Psychotherapy practice, the practitioner, and the profession – in sickness and in health - Tudor, Keith (Aporia, 2025)
Although the word psychotherapy, from the Greek (psyche + terapia) meaning soul healing, has multi-disciplinary roots, some of which date back to ancient Egyptian times, contemporary psychotherapy is predominantly aligned with health and healthcare. In response, the first part of the article interrogates the ideal of health and cure promoted by theories of psychotherapy; criticises the lack of critical practice regarding diagnosis; advocates a two continua approach to both sickness and health in psychotherapy; and argues that psychotherapy both is and is not a health practice. The second part of the article takes up the issue of the identity of psychotherapists and, by means of a review of different definitions of psychotherapy and of the more critical and radical traditions within the discipline and practice, argues that psychotherapists both are and are not health practitioners. The third and final part of the article offers a critical case study of the New Zealand Association of Psychotherapists’ application for the state registration of its practitioners; and argues that such regulation and registration compromises the profession of psychotherapy, and thus that psychotherapy both is and is not a health profession.